The EU Response to the «Refugee Crisis» of 2015 and Prospects for a Common EU Migration Policy - N. Bolshova (Международная аналитика)
The paper reviews the EU response to the recent «refugee crisis» through the theoretical lens of restrictive and preventive approaches and the concept of the «external dimension» in EU migration policy. The author examines the EU’s response as an indicator of the effectiveness of current EU migration policy under crisis situations caused by massive flows of migrants. According to the author, the European institutions have not been able to offer quick and effective «European solution». EU is late with the development, implementation of the policy measures as well as with bringing of them to the European public in an appropriate way, allowing to prevent social protests against asylum seekers. As a result the refugee crisis has caused «the crisis of solidarity» in the EU. There is a gap to state between the European values and real readiness of the EU to adhere to them. Instead the strategy of burden sharing between member-states EU implements the strategy of burden shifting on Turkey. The progress made by the EU in the field of communitarisation of migration policy could prevent neither the escalation of migration crisis, nor its negative consequences regarding the interim collapse of Schengen and Dublin systems. In this situation, the return to the intergovernmental approach in regulation of certain sensitive domains of EU migration policy is possible. The nature of the EU response confirms that the «external dimension» of migration policy has been implemented mostly through a restrictive approach, while a preventive approach has been marginalizing.